Efficacy and Safety of a Tri-Valent Ready-to-Use Porcine Circovirus Type 2a, Mycoplasma hyopneumoniae and Lawsonia intracellularis Vaccine in Weaned Pigs - Michelle Allen; Frank Roerink; Abigail Crowley; Susan Knetter; Chandra Morgan; Huiling Wei; Ruud Segers (Vaccines, 2025)
Background/Objectives: This study describes multiple trials demonstrating the safety and efficacy of a tri-valent vaccine against diseases caused by Porcine Circovirus Types 2a and 2d (PCV2a, PCV2d), Mycoplasma hyopneumoniae, and Lawsonia intracellularis. Methods: For each of the PCV2a and PCV2d onset of immunity (OOIs) and duration of immunity (DOI) studies, 25 pigs were vaccinated with a tri-valent vaccine and 25 with placebo. After dual challenge with PCV2a and porcine reproductive and respiratory virus (PRRSV) (OOI) or single challenge with PCV2d (OOI and DOI), respectively, viremia and lymphoid depletion data were collected. For each of the M. hyopneumoniae OOI and DOI studies, 35 to 70 pigs were vaccinated with the tri-valent vaccine and 35 to 70 with placebo. After M. hyopneumoniae challenge, the lungs were scored for disease. For the L. intracellularis OOI study, 40 to 50 pigs were vaccinated with the tri-valent and 40 to 50 with placebo. After L. intracellularis challenge, the intestines were scored for disease. All pigs were vaccinated at approximately 3 weeks of age, and all placebo vaccines were product matched. Results: Vaccinating pigs with a tri-valent vaccine reduced viremia and lymphoid depletion due to PCV2a and PCV2d, reduced lung lesions due to M. hyopneumoniae and reduced ileum and colonization scores due to L. intracellularis. Conclusions: The trials reported here demonstrated the safety and efficacy of the first ready-to-use PCV2, M. hyopneumoniae, and L. intracellularis vaccine for pigs.